2000
DOI: 10.1046/j.1460-9568.2000.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal actions of interleukin‐6 and brain‐derived neurotrophic factor on rat and mouse primary sensory neurons

Abstract: In low-density, serum-free cultures of neurons from embryonic rat dorsal root ganglia, interleukin-6 supports the survival of less than one third of the neurons yet virtually all of them bear interleukin-6 alpha-receptors. A finding that might explain this selectivity is that interleukin-6 acts on sensory neurons in culture through a mechanism requiring endogenous brain-derived neurotrophic factor. Antibodies or a trkB fusion protein that block the biological activity of brain-derived neurotrophic factor synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
52
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 45 publications
6
52
0
Order By: Relevance
“…This could be attributed to upregulation of overlapping functions with other neuropoietic cytokine receptors mediated by the common cytokine receptor subunit gp130. Indeed, IL-6 plays roles in neuronal survival and differentiation (März et al, 1997;Thier et al, 1999;Murphy et al, 2000) and Il6 gene deletion does not induce neuronal death (Cafferty et al, 2004). Consistent with redundancy, mice lacking individual members of IL-6 cytokine family display only mild phenotypes, as also observed in the present work, while animals lacking gp130 are not viable (Betz et al, 1998).…”
supporting
confidence: 87%
“…This could be attributed to upregulation of overlapping functions with other neuropoietic cytokine receptors mediated by the common cytokine receptor subunit gp130. Indeed, IL-6 plays roles in neuronal survival and differentiation (März et al, 1997;Thier et al, 1999;Murphy et al, 2000) and Il6 gene deletion does not induce neuronal death (Cafferty et al, 2004). Consistent with redundancy, mice lacking individual members of IL-6 cytokine family display only mild phenotypes, as also observed in the present work, while animals lacking gp130 are not viable (Betz et al, 1998).…”
supporting
confidence: 87%
“…One the other hand, this would not exclude the possibility that the electrophysiological changes ascribed to TNF-␣ contribute to synthesis of other survival-promoting factors such as BDNF. Recently, it has been described that the neuroprotective actions of interleukin-6, another proinflammatory cytokine that can influence neurotransmitter-operated ion currents (Qiu et al, 1995), on embryonic sensory neurons are mediated through a mechanism requiring endogenous BDNF (Murphy et al, 2000). Exogenously applied BDNF has been shown previously to prevent secondary RGC loss in our experimental paradigm .…”
Section: Discussionmentioning
confidence: 72%
“…Elevated levels of cytokine protein and mRNA (including IL-6) have been detected in embryonic serum and brain after MIA (Fidel et al, 1994;Cai et al, 2000;Urakubo et al, 2001;Gayle et al, 2004;Paintlia et al, 2004;Gilmore et al, 2005;Ashdown et al, 2006;Beloosesky et al, 2006;Meyer et al, 2006;Xu et al, 2006). IL-6 can regulate brain-derived neurotrophic factor (BDNF) expression (Murphy et al, 2000), and a decrease in BDNF is found in embryos and placentas 24 h after poly(I:C) administration (Gilmore et al, 2005). Thus, although the pleiotropic nature of IL-6 makes it difficult to predict the precise mechanism of action in the brain, many plausible pathways exist.…”
Section: Discussionmentioning
confidence: 99%